2013
DOI: 10.1080/02699931.2013.815154
|View full text |Cite|
|
Sign up to set email alerts
|

Biased attentional engagement with, and disengagement from, negative information: Independent cognitive pathways to anxiety vulnerability?

Abstract: Cognitive models of anxiety propose that selective attention to negative information plays a causal role in heightened anxiety vulnerability and dysfunction. However, there has been theoretical disagreement concerning whether anxiety-linked attentional biases reflect enhanced attentional engagement with, or impaired attentional disengagement from, negative information. We contend that previous methodologies have not been optimal in terms of their capacity to differentiate both types of bias. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 31 publications
4
87
2
Order By: Relevance
“…Fox et al (2001) showed that in contexts where the location of an upcoming visual target is largely predictable by a face-cue, it takes these individuals more time to re-orient attentional focus on (a minority of) trials where cues provided incorrect spatial information, but only for face-cues with an angry, but not neutral or happy, expression. While some researchers (e.g., Rudaizky, Basanovic, & MacLeod, 2014) suggest that impaired attentional disengagement from and enhanced attentional engagement to threat-related stimuli might have been jointly responsible for the described results, such findings nevertheless provide converging evidence for an attentional bias towards threatening information in anxious individuals. Similarly, trait-anxiety (TA) is associated with preferential encoding of threatening stimuli into memory without an intention to do so ("implicit-memory bias"; Mathews & MacLeod, 2005): Anxious individuals show better memory for task-irrelevant threat-related words presented during a lexical (but not a semantic) task (Russo, Fox, Lynn, & Nguyen-Van-Tam, 2001), and for task-irrelevant fearful faces in a face-identity recognition task (Stout, Shackman, & Larson, 2013).…”
Section: Attentional and Memory Biases In Anxious Individualscontrasting
confidence: 45%
“…Fox et al (2001) showed that in contexts where the location of an upcoming visual target is largely predictable by a face-cue, it takes these individuals more time to re-orient attentional focus on (a minority of) trials where cues provided incorrect spatial information, but only for face-cues with an angry, but not neutral or happy, expression. While some researchers (e.g., Rudaizky, Basanovic, & MacLeod, 2014) suggest that impaired attentional disengagement from and enhanced attentional engagement to threat-related stimuli might have been jointly responsible for the described results, such findings nevertheless provide converging evidence for an attentional bias towards threatening information in anxious individuals. Similarly, trait-anxiety (TA) is associated with preferential encoding of threatening stimuli into memory without an intention to do so ("implicit-memory bias"; Mathews & MacLeod, 2005): Anxious individuals show better memory for task-irrelevant threat-related words presented during a lexical (but not a semantic) task (Russo, Fox, Lynn, & Nguyen-Van-Tam, 2001), and for task-irrelevant fearful faces in a face-identity recognition task (Stout, Shackman, & Larson, 2013).…”
Section: Attentional and Memory Biases In Anxious Individualscontrasting
confidence: 45%
“…Belopolsky, Devue, and Theeuwes (2011) eliminated such a confound by presenting the (threat-) distractors at fixation and requiring an eyemovement to be made away from fixation to a target in the periphery. As it is unclear to what extend people engage with a stimulus at fixation, Rudaizky, Basanovic, and MacLeod (2014) have furthered this issue by using an exogenous cue to direct attention towards or away from the threat distractor and observed evidence for both rapid orienting towards and delayed disengagement from threats.…”
mentioning
confidence: 99%
“…To discriminate these two facets of attentional selectivity requires an experimental approach specifically designed to dissociate them. Grafton and MacLeod (2014) have recently developed the Attentional Response to Distal and Proximal Emotional Information (ARDPEI) task for precisely this purpose, and have demonstrated that it is capable of dissociating engagement and disengagement biases in anxious individuals (see also Rudaizky et al 2014). Appropriate variants of the ARDPEI task could be employed to determine whether the attentional bias to positive information associated with elevated positive affectivity reflects increased attentional engagement with, or impaired attentional disengagement from, such information.…”
Section: Discussionmentioning
confidence: 98%